PENGARUH KELOMPOK KRIMINAL BERSENJATA TERHADAP INTEGRASI NASIONAL DI PROVINSI PAPUA - Muhammad Al Fahrozi; Nova Elizhabeth; Naufal Maulana (Supremasi Hukum: Jurnal Penelitian Hukum, 2025)
The Papua Province is highly vulnerable to national integration conflicts due to its historically unique path of incorporation into the Unitary State of the Republic of Indonesia (NKRI), differing from other regions. One of the major current threats is the activity of separatist armed groups known as Armed Criminal Groups (KKB). This study aims to analyse the impact of KKB on national integration in Papua through a normative juridical approach, examining relevant laws and legal doctrines such as Law No. 5 of 2018 on the Eradication of Terrorism Crimes. The analysis reveals that KKB activities have seriously disrupted national security and unity, while also damaging the country's international reputation. The designation of KKB as a terrorist organisation is considered appropriate as it meets the legal criteria for terrorism. The study concludes that resolving the conflict in Papua cannot rely solely on military action but requires a comprehensive strategy that includes law enforcement, socio-cultural approaches, and diplomacy. It is recommended that the government enhance the effectiveness of Special Autonomy implementation, strengthen state presence in remote areas, and involve local leaders in national dialogue and reconciliation processes.